2013
DOI: 10.3390/lubricants1020022
|View full text |Cite
|
Sign up to set email alerts
|

Nanotribological Behavior of Carbon Based Thin Films: Friction and Lubricity Mechanisms at the Nanoscale

Abstract: The use of materials with very attractive friction and wear properties has raised much attention in research and industrial sectors. A wide range of tribological applications, including rolling and sliding bearings, machining, mechanical seals, biomedical implants and microelectromechanical systems (MEMS), require thin films with high mechanical strength, chemical inertness, broad optical transparency, high refractive index, wide bandgap excellent thermal conductivity and extremely low thermal expansion. Carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 122 publications
(120 reference statements)
1
19
0
3
Order By: Relevance
“…The standard method is capable of providing information on the elastic recovery and plastic deformation [12], with unprecedented lateral and sub-surface displacement resolution. Additionally, nanoindentation may also be used in measuring mechanical properties such as fracture behaviour [13], hardening, strain rate sensitivity, residual stress [14] and size effects in plasticity on a local level [15].…”
Section: Introductionmentioning
confidence: 99%
“…The standard method is capable of providing information on the elastic recovery and plastic deformation [12], with unprecedented lateral and sub-surface displacement resolution. Additionally, nanoindentation may also be used in measuring mechanical properties such as fracture behaviour [13], hardening, strain rate sensitivity, residual stress [14] and size effects in plasticity on a local level [15].…”
Section: Introductionmentioning
confidence: 99%
“…In general, hard coatings make the friction coefficient higher, because of their high interfacial shear strengths [15,16]. Among the hard coatings, DLC is becoming quite widely used, because of its low friction, superior wear resistance and simple composition (only C and H) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Among the hard coatings, DLC is becoming quite widely used, because of its low friction, superior wear resistance and simple composition (only C and H) [17,18]. DLC can be applied to machine component surfaces operating in dry, as well as lubricated conditions [16]. When DLC is applied to machine component surfaces operating in lubricated systems, conventional lubricants formulated for a steel/steel surface are still used for DLC coated surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that water acts as a lubricant for DLC coatings 19,23 . The lubricating action of the water can be explained as a result of a "three-body interaction" where the water reduces the adhesion between the surfaces in contact.…”
Section: Experimental Examplementioning
confidence: 99%
“…These amorphous films are a mix of sp 3 tetrahedral bonding (like in single-crystal diamonds) and sp 2 trigonal bonding (like in single-crystal graphite), and usually deposited by physical or chemical vapor deposition techniques 14 . Since Bhushan published the first nanotribological study of amorphous carbon films using an atomic force microscope (AFM) 15 , there have been many studies about the nanotribological properties of carbon-based coatings, as it has been reviewed for dry and lubricated conditions [16][17][18][19][20][21][22] . We can observe that for dry tests (Figure 8a), the friction coefficient decreases with the increase of the applied load from 10 µN to 100 µN, and stays constant when increasing from 100 µN to 1000 µN.…”
Section: Wear Ratio and Wear Ratementioning
confidence: 99%